Model Pembelajaran Treffinger Berbantuan Lembar Kerja Siswa dan Pengaruhnya terhadap Berpikir Kritis Siswa - Sahila Ridhiyani; sukardi sukardi; Masyhuri Masyhuri (Journal of Education, Humaniora and Social Sciences (JEHSS), 2022)
The purpose of this research is to determine whether Treffinger model, assisted by student worksheets, has an effect on students' critical thinking skills. This research uses the quantitative quasi-experimental research design with a matching control group pre-test and post-tests design. The research sample included two classes of 10th grade students of MAN, one experimental class and one control class, which were chosen at random after the classes were matched. The instrument is a critical thinking ability test that meets the questions' validity, reliability, discriminating power, and level of difficulty. All variables were quantitatively analysed using comparative analysis and Test-NGain. The research result shows that there are differences in critical thinking skills between the experimental and control groups. Considering the higher mean of the experimental class, it was concluded that the Trefinger model, assisted by worksheets, had an effect on students' critical thinking skills. The NGain analysis results also show that the experimental class increased in each dimension of critical thinking skills more than the control class. The implication is that this model strengthens and supplements the constructivist-oriented learning theory.